FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI ANAK BALITA DI KABUPATEN TIMOR TENGAH UTARA, PROVINSI NUSA TENGGARA TIMUR - Hadi Riyadi; Drajat Martianto; Dwi Hastuti; Evy Damayanthi; Kukuh Murtilaksono (Jurnal Gizi dan Pangan, 2011)
This research aims to analyze underlying factors affecting child malnutrition at Timor Tengah Utara district, NTT. The design was a cross-sectional study. Sample of this study was household that have underfive years old children residing in the areas of Plan International. Data was collected by using structured questionnaire, focus group discussion and in-depth interview. Nutritional status was measured using anthropometric measurement with weight and height indicators and child consumption was recorded using 24 hours food’s recall. Result showed that in three villages prevalence of malnourished children was high, which were 6.0% classified as severe underweight, 15.3% severe stunting and 0.7% severe wasting. There was no significant difference in term of nutritional status. Child malnutrition was influenced by low access to nutrition and health information, low nutrition knowledge and practices, and low family income.